Kontribusi Motivasi Menyelesaikan Masalah dan Komunikasi Interpersonal terhadap Strategi Pemecahan Masalah Siswa Sekolah Menengah - Minarsi Minarsi; Herman Nirwana; Yarmis Syukur (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
This research was conducted from the student low level toward student problem solving strategies. The student problem solving strategies were affected by motivation problem to resolve and interpersonal communication. This research was intended to describe: (1) the motivation of students in problem solving, (2) student interpersonal communication, (3) the student problem solving strategies, (4) the contribution of the motivation problem to resolve  toward student problem solving strategies (5) the contribution of the interpersonal communication toward student problem solving strategies, and (6) the contribution of the motivation problem to resolve and interpersonal communication toward student problem solving strategies.This correlational descriptive research applied quantitative methods. The population of this research were 601 students of SMA Negeri 2 Pariaman on grade XI and XII, also 240 students there were chosen by proportional stratified random sampling technique.